Clinical Significance of Blastocystis Sp. among Children with Leukemia - khalil, Zainab Khalid (AL-Kindy College Medical Journal, 2019)
Background: Blastocystis spp. distributes world widely and the genus Blastocystis include many subtypes that are isolated from human intestinal tract. It is considered the most common parasite detected in human being. Objectives: To evaluate the incidence of Blastocystis spp. among leukemic children, to find out its association with the presence of symptoms (diarrhea and abdominal pain), and to assess the efficacy of different staining methods in detection of Blastocystis spp. Type of the study: cross-sectional study. Method: 103 children were enrolled in this study, 53 leukemic patients and 50 healthy controls. The study was performed during the period between January and June 2014, in Oncology department of Ibn Al-Atheer teaching hospital in Mosul city. Three consecutive samples were taken from each child and a thorough history was taken from them. The samples then treated with 3 stains, iodine, iron hematoxylin, and trichrome.The data was analyzed using minitab version 17, Fischer’s exact test, Two-proportions test, and Correlation test. The results were considered statistically significant with P-value <0.05. Results: Blastocystis spp. was detected in 18.87% of leukemic children and in 10% of healthy group. All specimens were stained by iodine, iron hematoxylin, and trichrome stains. Infection rates among patients were (9.4%, 11.3%, and 18.87% respectively) while among healthy children they were (4%, 6%, and 10% respectively). However, these differences were statistically nonsignificant. A higher infection rate was detected in the preschool children (33.3%) than school age group (6.9%). Furthermore, there was a significant association between Blastocystisspp. infection and intestinal symptoms (abdominal pain and diarrhea). Conclusion: Our study reveals a higher rate of infection with Blastocystis spp. among leukemic children than normal controls and a significant association was seen between incidence ofBlastocystisspp. infection and symptomatic children. Those results draw attention for the significance of Blastocystis spp. infection in immunosuppressed patients and lighten the way for further studies on its pathogenicity and diagnostic methods.